Enhancing Communicative Competence in Foreign Language Learning through Artificial Intelligence Technology - Yusuf, Rusydi Muhammad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This article explores the evolution of approaches in English language teaching, starting from traditional approaches, communicative approaches, and culminating in the integration of Artificial Intelligence (AI)-based approaches. Traditional approaches, which emphasize linguistic structures and forms, have proven insufficient in achieving the main goal of language education—enhancing students’ oral and written communication skills. As a response, the communicative approach emerged, focusing on meaningful language use in real contexts and centering learners as active participants in the learning process. Over time, the communicative approach has been enriched by the integration of AI, which offers personalization, interactivity, and efficiency through tools such as chatbots, virtual assistants, and automated evaluation systems. AI enables more adaptive learning, instant feedback, and a more authentic language learning experience. Nevertheless, integrating AI into language education also presents challenges, including technological accessibility gaps, the need for teacher training, and concerns regarding data ethics. This article concludes that a hybrid model combining communicative and AI-based approaches can create more effective and relevant English language instruction in the digital age, provided it is supported by inclusive educational policies and well-prepared human resources